Digital transformation evaluating emerging technologies - Daim, Tugrul Unsal 1967- (World Scientific series in R&D management, 2020)
Selecting the right technology is one of the most critical decisions in technology driven enterprises, and no selection is complete without a thorough and informed evaluation. This book explores the digital transformation movement from three perspectives : the technological, the personal, and the organizational. The technical perspective analyses and evaluates new and up and coming technologies such as IoT and Cloud Technology. The personal perspective focuses on the consumer's attitude and experience in the adoption of technologies such as smart homes, smart watches, drones and wireless devices. And the organizational perspective focuses on evaluating how technology-driven an organization and their core activities or products are. This book is an ideal reference for managers who are responsible for digital transformation in their organizations and also serves a good starting point for researchers interested in understanding the trend. The book contains case studies that may be used by educators in MBA and Engineering and Technology Management MS programs covering digital transformation related courses"--